Wild Brazilian species of Eugenia genera (Myrtaceae) as an innovation hotspot for food and pharmacological purposes. (July 2019) - de Araújo, Fábio Fernandes; Neri-Numa, Iramaia Angélica; de Paulo Farias, David; da Cunha, Gabryelle Rahyara Miranda Castro; Pastore, Glaucia Maria
Abstract: The Myrtaceae is one of the most common plant families in Brazil, including >1000 species of native fruit spread from North to South, where around 50% of all species are endemic to the Atlantic Rain Forest Biome. Most Brazilian species belong to Eugenia, Campomanesia, Psidium and Myrciaria genera. In general, they are characterized by the presence of leaves opposite, simple, entire, with pellucid glands containing ethereal oils and produces berry-like, fleshy fruits with a wide diversity of beneficial characteristics. Several parts of these plants are widely used in regional folk medicine as an astringent, anti-inflammatory, antihypertensive, to treat gastrointestinal disorders, and so on. Some species have already been studied and most of their metabolic effects are attributed to the presence of polyphenols, carotenoids as well as sesquiterpenes and monoterpenes. In addition, the Myrtaceae family has great economic potential, because of the sensory characteristics which encourages their commercial exploitation plus the presence of phytochemicals which play an important role in managing several degenerative chronic diseases besides representing a hotspot of technological innovation for food, cosmetic and pharmaceutical purposes. In this context, this review discusses about the importance of some Eugenia genera representatives such as Eugenia uniflora, Eugenia stipitata, Eugenia brasiliensis, Eugenia pyriformis and Eugenia dysenterica, emphasizing its profile of bioactive compounds as well as the knowledge of the nutritional and functional fruit potential, providing information for further studies aiming to stimulate the cultivation of Brazilian wild berries, for consumption and new food ingredients. Graphical abstract: Unlabelled Image Highlights: Eugenia fruits are good sources of volatile and phenolic compounds. Brazilian wild berries represent a good source of bioactive compounds. They can be used in the prevention or treatment of chronic degenerative diseases. Brazilian wild berries intake is linked to anti-inflammatory and anti-glycemic modulation. Brazilian wild berries can provide health benefits such as "superfruits" from temperate regions.